Proceedings of 3rd International Sustainable Buildings Symposium (ISBS 2017) Volume 1 - Fırat, Seyhan; Kinuthia, John.; Abu-Tair, Abid.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2018)
This book describes the latest advances, innovations, and applications in the field of building design, environmental engineering and sustainability as presented by leading international researchers, engineers, architects and urban planners at the 3rd International Sustainable Buildings Symposium (ISBS), held in Dubai, UAE from 15 to 17 March 2017. It covers highly diverse topics, including smart cities, sustainable building and construction design, sustainable urban planning, infrastructure development, structural resilience under natural hazards, water and waste management, energy efficiency, climate change impacts, life cycle assessment, environmental policies, and strengthening and rehabilitation of structures. The contributions amply demonstrate that sustainable building design is key to protecting and preserving natural resources, economic growth, cultural heritage and public health. The contributions were selected by means of a rigorous peer-review process and highlight many exciting ideas that will spur novel research directions and foster multidisciplinary collaboration among different specialists.
The Using Waste Concretes As Recycling Aggregate In Concrete Production And Sustainability -- A comprehensive study on the effect of households' evolution on residential energy consumption patterns -- Liquefaction Analysis by Using Laboratory Scale Shaking Table Test Device -- Impacts of Foundation on Embodied Carbon in Structures -- Enhancement of Physicochemical Properties of Dubai's Sand to Conserve Irrigation Water -- Dynamic Analysis of a Reinforced-Concrete Post Tensioned Wind Turbine Tower -- Evaluation of Sustainable Education Buildings on Samples -- The importance of Geological conditions effects on construction in landscape planning in Turkey -- An overview of the signs and graphical representations used in Smart Buildings & Cities -- Review of Liquefaction Around Marine and Pile-Supported Wharf Structures -- Impacts Of Bleaching And Varnishing Process On The Amount Of Co2 In Scotch Pine (Pinus Sylvestris Lipsky) Wood Material -- Experimental Investigation Of Impact Behavior Of Engineered Cementitious Concrete Beam.
Keywords: Buildings -- Design and construction; Sustainability; Energy policy; Energy and state; Climatology; Building Construction and Design; Sustainability; Energy Policy, Economics and Management; Climate Sciences